A broad-spectrum novel bacteriocin produced by Lactobacillus sakei in Nanjing Steamed Roast Duck: Purification, antimicrobial characteristics, and antibacterial mechanisms. (December 2022) - Fu, Yuan; Zhao, Dongbing; Wang, Liyan; Jiang, Guochuan; Liu, Xuejun
Abstract: A new bacteriocin (Y19-2) was isolated, purified, and characterized from Nanjing Steamed Roast Duck, a traditional Chinese fermented meat product. Purification was performed via ammonium sulfate fractional precipitation, diethyl aminoethyl (DEAE)-52 cellulose ion-exchange chromatography, Sephadex G-50 chromatography, and reversed-phase high-performance liquid chromatography (RP-HPLC). SDS-PAGE analysis showed the molecular weight of Y19-2 is 20 kDa, making it fall into the third type of bacteriocin based on the classifications of bacteriocins according to their molecular weights. In addition, Y19-2 is heat-resistant as suggested by a merely 14% loss of its antibacterial activity when heated at 121 °C for 30 min. In acidic conditions (pH 3–5), Y19-2 has obvious antibacterial activity against both gram-positive and gram-negative bacteria, and such an activity can be partially inactivated by pepsin and trypsin while being completely inhibited by papain. Scanning electron microscopy and differential thermal scanning analysis showed that Y19-2 could inhibit bacteria growth by destroying the bacterial cell wall and affecting the synthesis of bacteria's nucleic acids. Therefore, Y19-2 is potential as a bioprotective agent in foods. Highlights: A novel III bacteriocin Y19-2 was purified. Y19-2 was a broad-spectrum, heat-resistant and protease-inactivated bacteriocin. Y19-2 could inhibit bacteria growth by destroying bacterial cell wall and affecting synthesis of bacteria's nucleic acids.